2001
DOI: 10.1046/j.1537-2995.2001.41060803.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusions in the neonatal intensive care unit:factors predicting which patients will require multiple transfusions

Abstract: NICU patients with liver disease or renal insufficiency who receive one platelet transfusion are likely to receive additional transfusions. Therefore, these patients constitute a possible study population for a Phase I/II rTPO trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 33 publications
4
101
0
Order By: Relevance
“…Thus, whether the longer bleeding times among the earliest gestation neonates contribute in any way to hemorrhages remains speculative. 11,12 Many recent reports, [13][14][15][16][17] including studies by our group, [14][15][16][17] indicate that neonatologists sometimes order platelet transfusions for nonbleeding neonates whose platelet counts are in the 100 000 to 150 000 per microliter range. This range is sometimes called 'mild' thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, whether the longer bleeding times among the earliest gestation neonates contribute in any way to hemorrhages remains speculative. 11,12 Many recent reports, [13][14][15][16][17] including studies by our group, [14][15][16][17] indicate that neonatologists sometimes order platelet transfusions for nonbleeding neonates whose platelet counts are in the 100 000 to 150 000 per microliter range. This range is sometimes called 'mild' thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several publications have begun to define risks of platelet transfusions in neonates. [13][14][15][16][17][18] Thus, it is possible that nonbleeding neonates with mild thrombocytopenia who receive platelet transfusions are subjected to transfusion risks but derive no transfusion benefits. In the present study, we found no prolongation of the bleeding time among neonates with mild thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…22 They are also recommended as prophylaxis against bleeding if the count falls sufficiently low. [23][24][25] Precisely how low to permit a platelet count to fall in an ELBW neonate before ordering a platelet transfusion is not known. We found that platelet transfusions were nearly always given for prophylaxis against bleeding rather than to treat active bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…However, transfusions unquestionably carry risks, and multiple transfusions compound these risks. [3][4][5][6][7] It is highly probable that some transfusions given to Neonatal Intensive Care Unit (NICU) patients are not necessary. Such transfusions, although ordered with good intentions, might convey no benefits to the recipient, but nevertheless carry risks.…”
Section: Introductionmentioning
confidence: 99%